Analysis of Students’ Understanding About Education for Sustainable Development in Green Chemistry-Based Organic Chemistry Laboratory Innovations in The Digital Era - Mimilaida Mimilaida; Wawan Wahyu; Iqbal Musthapa (FKIP - Universitas Riau, 2026)
Education for Sustainable Development (ESD) is essential for promoting sustainability-oriented learning in chemistry education. This study aimed to analyze chemistry education students’ understanding, perceptions, and learning needs regarding the integration of ESD in Green Chemistry-based organic chemistry laboratory learning in the digital era. A descriptive survey was conducted with 134 chemistry education students using a validated five-point Likert-scale questionnaire distributed through Google Form. Data were analyzed descriptively using mean scores and percentages. The results showed that students’ understanding of ESD was moderate (mean = 3.00; 60%), while their perceptions of Green Chemistry implementation (mean = 3.30; 66%), sustainability relevance (mean = 4.00; 80%), sustainability understanding (mean = 3.70; 74%), and digital innovation (mean = 4.15; 83%) were positive. Students also expressed a very high need for additional ESD-related learning materials (mean = 4.25; 85%). The findings provide empirical evidence of a gap between students’ positive perceptions of sustainability-oriented laboratory learning and their conceptual understanding of ESD, suggesting that engagement in sustainability-oriented laboratory practices does not automatically translate into a comprehensive understanding of ESD concepts. Therefore, chemistry educators and curriculum developers should strengthen the integration of ESD concepts through digital resources and explicit instructional strategies in organic chemistry laboratory education.